2006
DOI: 10.1007/s10265-006-0042-3
|View full text |Cite
|
Sign up to set email alerts
|

Cd-induced growth reduction in the halophyte Sesuvium portulacastrum is significantly improved by NaCl

Abstract: The effects of Cd(2+) and NaCl, applied together or separately, on growth and uptake of Cd(2+) were determined for the halophyte Sesuvium portulacastrum L. Seedlings were cultivated in the presence of 50 or 100 micromol L(-1) Cd(2+) alone or combined with 100 or 400 mmol L(-1) NaCl. Data showed that alone, Cd(2+) induced chlorosis, necrosis, and inhibited growth. Addition of NaCl to Cd(2+)-containing medium restored growth and alleviated the toxicity, however. NaCl also enhanced the amounts of Cd(2+) accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…BCF indicates the efficiency of a plant species in accumulating a metal into its tissues from the surrounding environment (Ladislas et al 2012). TF indicates the efficiency of the plant in translocating the accumulated metal from its roots to shoots (Ghnaya et al 2007). Metal extraction amount indicates the metal amount which the whole plant tissue extracted from the contaminated soil at the harvest time.…”
Section: Accumulation and Tolerance Of M Cordatamentioning
confidence: 99%
“…BCF indicates the efficiency of a plant species in accumulating a metal into its tissues from the surrounding environment (Ladislas et al 2012). TF indicates the efficiency of the plant in translocating the accumulated metal from its roots to shoots (Ghnaya et al 2007). Metal extraction amount indicates the metal amount which the whole plant tissue extracted from the contaminated soil at the harvest time.…”
Section: Accumulation and Tolerance Of M Cordatamentioning
confidence: 99%
“…NaCl addition increased Cd uptake and translocation in Sesuvium portulacastrum (Ghnaya et al, 2007), wheat , and cole (Raziuddin et al, 2011). Chai et al (2013) reported that addition of a moderate concentration of NaCl significantly increased Cd content in shoots and roots of halophyte Spartina alterniflora.…”
Section: Article In Pressmentioning
confidence: 96%
“…Wherein, the growth reduction at high salinity was essentially due to nutritional disruption by salt. Furthermore, plants exhibit the highest accumulation capacity for heavy metals like cadmium (Cd), providing its importance in the environment protection by the extraction of heavy metals from salty contaminated soils (Ghnaya et al 2005). Slama et al (2007) found that, the system is also useful to study the drought stress caused by mannitol and PEG with elevated levels of osmolytes and reduced growth in osmotically stressed plants.…”
Section: Utilizationmentioning
confidence: 99%